Gray matter volume increase in the retrosplenial/posterior cingulate cortices of blind soccer players - Morita, Tomoyo; Naito, Eiichi (Frontiers in Neuroscience, 2025)
Individuals typically recognize where they are (localization) and in which direction they are heading (orientation) in a space using vision, and the retrosplenial/posterior cingulate cortices (RSC/PCC), parahippocampal cortex (PHC), and hippocampus (HP) have been shown to play crucial roles for these navigation-related functions. However, there is empirical evidence that top blind soccer players with long-term training can navigate on the court without vision. This study examined the potential changes in gray matter (GM) volume in the RSC/PCC, PHC, and HP in the brains of a leading and other blind soccer players. We collected structural magnetic resonance imaging (MRI) scans from six blind soccer players (including the world’s top player) and eight blind non-soccer players. Using voxel-based morphometry (single-case approach), we compared GM volume in each participant to that of 250 sighted participants (none of whom had ever played blind soccer). The world’s top blind soccer player had a significant increase in GM volume in the bilateral RSC/PCC compared to sighted participants. Two of the other five blind soccer players also showed a GM increase in the left RSC/PCC. However, this increase in GM volume was not observed in blind non-soccer players. Consequently, the probability of a significant GM increase in the RSC/PCC was significantly higher in the blind soccer group than in the blind non-soccer group. In contrast, no between-group differences were observed in the probability of a significant GM volume increase in the PHC and HP. This study, which unveiled the characteristics of the brains of the world’s top blind soccer player and other blind soccer players, demonstrates for the first time that blind soccer training, which requires navigation based on non-visual cues, may enlarge the human RSC/PCC. Moreover, the findings promote our understanding of the brains of visually-impaired persons playing blind soccer.